(untitled) (Studia Prawnicze / The Legal Studies, 1967)
The subject of the paper are the relations between parents and their children, the problems of adoption, guardianship, and tutelage in agreements on mutual legal turnover that Poland, German Democratic Republic, Roumanian People’s Republic, and the Soviet Union have ’concluded with other socialist countries. With regard to the relations between parents and their children most agreements comprise separate enactments concerning relations between parents-married couple and their children and between parents and their children born out of marriage. In contracts regarding the relations between parents and their children born in marriage appear three types of points of contact, namely : common nationality of parents and their children, nationality of a child, and common domicile of parents and their children. The relations between parents and their children born out of marri age are in all types of contracts subjected to the same point of contact, i. e. the law of a child’s nationality. Six from 23 contracts under examination comprise enactments that are common for relations between parents and their children in both mentioned categories. Besides fundamental question of the extension and connection the problem of adoption has been approached with regard to the question of consent for adoption, adoption by a married couple, and the jurisdiction in such cases. In all contracts on adaption the same point of contact is taken into account, i.e. the nationality of an adopting person. The agreement between Yougoslavia and Poland is an exception since it requires that substantial law of both countries-parties in the agreement be jointly employed. In the case a guardianship or tutelage is to be enacted or abolished, and in casses for determining legal relations between a guardian or a curator and a pupil, in all contracts the principle of employing the law of pupil’s nationality is accordingly accepted. Guardianship and tutelage involve, hovewer, a lot of problems that are solved according to independent types of points of contact and the appropriate principles. These are: the duty to accept a guardianship, intervention of guardianship authority in questions of the guardianship referring to a pupil who is a citizen of the country-party in an agreement, interim orders, conveyance of a guardianship, the extension of a guardian’s authority, charging as a guardian a citizen of the country-party in an agreement, change of domicile made by a pupil into the other country-party in an agreement after the guardianship is enacted, and the case when a pupil has a property in the area of the other country-party in a contract.